PENERAPAN MODEL STAD UNTUK MENINGKATKAN HASIL BELAJAR PPKN KELAS X SMA 10 PONTIANAK - Dwi Lestari, Syhinta Bella; Okianna, Okianna; Atmaja, Thomy Sastra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aims to improve learning outcomes by using the Student Team Achievement Division (STAD) model in Civic Education subjecttowards 10th-grade Social 1students of Senior High School 10 Pontianak. This is a classroom action research with the descriptive method. The research was conducted at the senior high school 10 Pontianak, engaging 34 10th-grade students of Social 1 as the research subject. The data collection techniques used are observation, measurement and documentary study techniques. The data collection tools used are observation sheets and learning outcomes tests. The data were analyzed by calculating the averages and percentages. Conducted in III cycles, the average scores showed improvements in Cycle II and III.The average score in Cycle I was only 66,47, with only 26,48% or 9 out of 34 students passed the minimum completeness criteria (KKM). Respectively, the average scores in Cycle II and III are 71,76 and 87,94 with the number of students passing the KKM as many as 18 and 28 or 52,95% and 82,35% in percentage. Based on the data analysis, it shows that STAD model can improve learning outcomes to the 10th-grade students of Social 1 of Senior High School 10 Pontianak in civic education subject. Keywords: Application, STAD, Learning Outcomes, Civic Education